2018
DOI: 10.1021/acs.chemrestox.8b00307
|View full text |Cite|
|
Sign up to set email alerts
|

Plasma and Hepatic Concentrations of Chemicals after Virtual Oral Administrations Extrapolated Using Rat Plasma Data and Simple Physiologically Based Pharmacokinetic Models

Abstract: Only a small fraction of chemicals possesses adequate in vivo toxicokinetic data for assessing potential hazards. The aim of the present study was to model the plasma and hepatic pharmacokinetics of more than 50 disparate types of chemicals and drugs after virtual oral administrations in rats. The models were based on reported pharmacokinetics determined after oral administration to rats. An inverse relationship was observed between no-observed-effect levels after oral administration and chemical absorbance ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
91
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(91 citation statements)
references
References 48 publications
0
91
0
Order By: Relevance
“…To estimate the permeability of dihydrocodeine in human jejunum, its apparent permeability in a Caco‐2 monolayer system was determined following the reported method (Kamiya et al, ). The in vitro kinetic parameters for dihydrocodeine were experimentally determined using recombinant human P450 2D6/3A4 (Uehara et al, ) and UGT2B4/2B7 (Uno et al, ), according to our reported methods.…”
Section: Methodsmentioning
confidence: 99%
“…To estimate the permeability of dihydrocodeine in human jejunum, its apparent permeability in a Caco‐2 monolayer system was determined following the reported method (Kamiya et al, ). The in vitro kinetic parameters for dihydrocodeine were experimentally determined using recombinant human P450 2D6/3A4 (Uehara et al, ) and UGT2B4/2B7 (Uno et al, ), according to our reported methods.…”
Section: Methodsmentioning
confidence: 99%
“…Simplified PBPK models for styrene (molecular weight: 104.15) consisted of a chemical receptor (gut) compartment, a metabolizing (liver) compartment, and a central compartment with a peripheral compartment and were established as previously described (Kamiya et al, 2019;Yamazaki et al, 2016). The octanol-water partition coefficient (logP: 2.86) and the plasma unbound fraction (f u,p : 0.136) of styrene were estimated in silico using ChemBioDraw and Simcyp (Emoto et al, 2009).…”
Section: Estimation Of Plasma and Liver Concentrations Using Simplifimentioning
confidence: 99%
“…The concentrations of styrene in plasma were also taken from the literature (Withey, 1976). The volume of the systemic circulation (V 1 ), the absorption rate constant (k a ), and the in vivo hepatic intrinsic clearance (CL h,int ) were evaluated using nonlinear regression analysis fitting techniques, as described previously (Kamiya et al, 2019). The renal clearance (CL r ) was set at a minimum value compared with the hepatic clearance (CL h ).…”
Section: Estimation Of Plasma and Liver Concentrations Using Simplifimentioning
confidence: 99%
See 1 more Smart Citation
“…However, such PBPK models are impractical for widespread daily use in clinical hospital pharmacies to support the care of a verity of patients. Against this background, we proposed simple PBPK models for drugs for practical use by paramedical staff [8]. A prototype PBPK simulator [9] for creating the visualized plasma concentration curves for important medicines by easy input was provided by our group and has been currently updated and modified.…”
Section: Introductionmentioning
confidence: 99%